2007
DOI: 10.1074/jbc.m702289200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Prostaglandin Reductase Reveals the Involvement of Prostaglandin E2 Catabolism in Regulation of Peroxisome Proliferator-activated Receptor γ Activation

Abstract: This report identifies a novel gene encoding 15-oxoprostaglandin-⌬ 13 -reductase (PGR-2), which catalyzes the reaction converting 15-keto-PGE 2 to 13,14-dihydro-15-keto-PGE 2 . The expression of PGR-2 is up-regulated in the late phase of 3T3-L1 adipocyte differentiation and predominantly distributed in adipose tissue. Overexpression of PGR-2 in cells decreases peroxisome proliferator-activated receptor ␥ (PPAR␥)-dependent transcription and prohibits 3T3-L1 adipocyte differentiation without affecting expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
96
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 38 publications
(51 reference statements)
9
96
0
Order By: Relevance
“…A unique aspect of PTGR2 action was revealed in studies that indicated a unique link between PGE2 catabolism and regulation of ligand-induced PPAR gamma activation of adipogenesis (Chou et al, 2007). For instance, overexpression of PTGR2 represses transcriptional activity of PPARG and inhibits 3T3-L1 adipocyte differentiation (Chou et al, 2007). These observations on PTGR2 coupled with the age-associated increase in adipose tissue PTGR1 in this study may indicate that PTGR1 may have a role in adipogenesis in porcine adipose tissue.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…A unique aspect of PTGR2 action was revealed in studies that indicated a unique link between PGE2 catabolism and regulation of ligand-induced PPAR gamma activation of adipogenesis (Chou et al, 2007). For instance, overexpression of PTGR2 represses transcriptional activity of PPARG and inhibits 3T3-L1 adipocyte differentiation (Chou et al, 2007). These observations on PTGR2 coupled with the age-associated increase in adipose tissue PTGR1 in this study may indicate that PTGR1 may have a role in adipogenesis in porcine adipose tissue.…”
Section: Discussionmentioning
confidence: 50%
“…Enzyme assays detected PTGR1 activity in a number of swine tissues, but adipose tissue contained the highest PTGR1 specific activity (Anggard et al, 1971). It is important to consider information on another Pig adipose tissue genes prostaglandin reductase, that is, PTGR2, which is also a 15-oxoprostaglandin 13-reductase (Chou et al, 2007) as both PTGR1 and PTGR2 are predominantly distributed in adipose tissue and both catalyze the NADH/NADPH dependent reduction of the D 13 double bond of 15-ketoprostaglandins to yield 15-keto-13,14-dihydroprostaglandins which results in a further reduction of the biological activities of prostaglandins. Furthermore, mouse PTGR2 protein has 40% amino acid sequence identity with mouse PTGR1 and human PTGR1 (Chou et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations